EFFICIENT MAJORITY LOGIC DECODING OF EUCLIDEANGEOMETRY LOW DENSITY PARITY CHECK (EG-LDPC) CODES: ERROR DETECTION - et. al, anvesh Thatikonda (International Journal of Advanced Science and Technology, 2020)
Low density parity check codes are utilized to identify whether a word has errors in the principal emphases of dominant part rationale decoding, and when there are no errors the decoding closes without finishing the remainder of cycles. A strategy was proposed to quicken the lion’s share rationale decoding of distinction set low density parity check codes. It is valuable as dominant part rationale decoding can be actualized sequentially with basic equipment yet requires an enormous decoding time. This task objective is to diminish the decoding time by halting the decoding procedure when no errors are identified. In the primary cycle, errors will be distinguished when at any rate one of the check equations is influenced by an odd number of bits in error. In the subsequent emphasis, as bits are consistently moved by one position, errors will influence different equations with the end goal that a few errors undetected in the main cycles will be identified. Result shows that a word can be perused from a memory ensured with one stage MLD EG-LDPC codes, and influenced by up to four bit errors, and every one of these errors can be recognized in just three decoding cycles.